Comparison of Site Localization Techniques for Brain Stimulation. Issue 2 (June 2019) - Nikolin, Stevan; D'Souza, Olav; Vulovic, Vedran; Alonzo, Angelo; Chand, Nicholas; Dong, Vanessa; Martin, Donel; Loo, Colleen
Abstract : Objectives: The dorsolateral prefrontal cortex (DLPFC) is a commonly targeted site using noninvasive brain stimulation techniques. Methods used to localize this site commonly rely on the International 10–20 electroencephalography (EEG) system, including elastic EEG caps, which stretch to accommodate varying head sizes, as well as the Beam F3 algorithm, which uses scalp measurements to calculate the location of the DLPFC. Both methods have been validated against magnetic resonance imaging–based DLPFC localization and are regularly used in research centers and clinics, but an in vivo comparison of reliability has not yet been conducted. This study examines whether Beam F3 and EEG cap methods differ in DLPFC localization, when applied by different practitioners (measurers) on a range of subjects. Further, whether measurer experience or subject head characteristics influence localization. Methods: Measurers (n = 5) of varying levels of experience identified the location of the left DLFPC on subjects (n = 6) with varying head sizes, using both Beam F3 and EEG cap methods. An independent assessor recorded the measurers' placements along the anterior-posterior and medial-lateral planes. Values were normalized to the subjects' mean nasion-inion and tragus-tragus distances and examined using a mixed effects repeated measures analysis. Results: The Beam F3 method resulted in significantly more anterior placements (~11.5 mm) compared with the EEG cap. Subjects with smaller head sizes had more anterior placements, compared with medium and large heads, regardless of the method used. There was no significant difference between methods along the medial-lateral plane. Measurer experience did not significantly influence DLPFC localization. Conclusions: Beam F3 and EEG cap methods resulted in similar DLPFC placements, with a small difference along the anterior-posterior plane. Measurer experience did not affect either method, suggesting that 2 weeks of training is sufficient to achieve competency. Training and reliability of DLPFC placement therefore do not represent substantial barriers to application of either method. Special care should be taken with subjects with small heads as both methods resulted in more anterior DLPFC placements.